Matthew S. Goldstone. The Dangerous Duty of Rebuke: Leviticus 19:17 in Early Jewish and Christian Interpretation. Supplements to the Journal for the Study of Judaism 185 - Akiyama, Kengo (Studies in Christian-Jewish Relations, 2020)
No abstract is available.